Buchdruck und Reformation in Bern - Schlüter, Sabine (Enthalten in:Zwingliana;Zürich : TVZ, Theologischer Verlag Zürich, 1897;45(2018), Seite 203-232, 2018)
Paving the way towards Reformation in Berne was a process set by the authorities, but it disunited the members of the Council. They empowered themselves on clerical and theological issues which overextended their competency. In the first five years (1538-1523) they underestimated the phenomenon of book printing as a powerful means of mass communication that quickly made the literate middle and upper classes - members of the council as well - understand what the new doctrine was all about. From 1523 on the Council itself used printing to consolidate its own authority. A censorship act set boundaries in the Bernese printing business as from 1539.
Zusammenfassung in englischer Sprache
Keywords: Reformation; Bern; Buchdruck; Reformationsmandat; Adolf Fluri; Adam Petri; Christoph Froschauer; Mathias Apiarius; Christoph von Diesbach; Rat von Bern; Zensur